1998
DOI: 10.1002/(sici)1096-8628(19981102)80:2<103::aid-ajmg2>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

An adult with 49,XYYYY karyotype: Case report and endocrine studies

Abstract: Sex chromosome abnormalities, such as 47,XXX, 47,XXY, 47,XYY, and 45,X, are relatively common and occur in approximately 1 of 400 births. Sex chromosome tetrasomy and pentasomy are much rarer events. The somatic and developmental consequences of supernumerary sex chromosomes have not been studied adequately. This is especially true of individuals with only supernumerary Y chromosomes. Based on available case reports, the effects of extra Y chromosomes appear not as severe as those of supernumerary X chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Those from Van den Berghe et al [1968] (86%), Plauchu et al [1984] (96.7%), and Kyriakakos et al [1995] (93.5%) are cases with tetrasomy Y representing the major cell line within a mosaic. Finally, the cases reported by Sirota et al [1981], Noël et al [1988], and Shanske et al [1998] are nonmosaic cases. While no pentasomy Y has been reported, Das et al [1993] have reported a 49,XXYYY patient.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Those from Van den Berghe et al [1968] (86%), Plauchu et al [1984] (96.7%), and Kyriakakos et al [1995] (93.5%) are cases with tetrasomy Y representing the major cell line within a mosaic. Finally, the cases reported by Sirota et al [1981], Noël et al [1988], and Shanske et al [1998] are nonmosaic cases. While no pentasomy Y has been reported, Das et al [1993] have reported a 49,XXYYY patient.…”
Section: Discussionmentioning
confidence: 91%
“…One adult with tetrasomy Y (aged 30) was described previously with hypogonadism and infertility [Shanske et al, 1998]. All other patients were young boys with normal genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…CT scan results were reported in a 22-yearold nonmosaic 49,XYYYY male who appeared to be having moderate to severe intellectual disability. Although he had normal head size in the 75th centile, CT scan results showed bilateral ventricular enlargement and diffuse cortical atrophy [Shanske et al, 1998]. A postmortem report from a 28-weekold 49,XYYYY fetus also found abnormalities, including a hypoplastic corpus callosum and a small cerebellum with a large cyst [Frey-Mahn et al, 2003].…”
Section: Scas With More Than One Additional X or Y Chromosomementioning
confidence: 99%
“…Individuals with more than one supernumerary Y chromosome are presumably very rare [Mazauric‐Stuker et al, 1992; Shanske et al, 1998]. We are aware of only three published cases with an apparently non‐mosaic 49,XYYYY chromosome count [Sirota et al, 1981; Noel et al, 1988; Shanske et al, 1998]. Plauchu et al [1984] reported an additional patient with four Y chromosomes in the overwhelming majority of cells investigated and a second cell line with three Y chromosomes.…”
Section: To the Editormentioning
confidence: 99%
“…Clinical information on affected individuals is very limited due to the small number of observations (Table I). The only brain anomalies diagnosed so far were dilated lateral ventricles and cortical atrophy [Shanske et al, 1998]. A unilateral porencephalic cerebral cortical cyst was reported, however, in a fetus after prenatal diagnosis of 45,X/48,XYYY mosaicism and termination of pregnancy at 20 weeks gestation [Bryke et al, 1989].…”
Section: To the Editormentioning
confidence: 99%